Influence of YouTube Finance Influencers and Traders’ Tips on Investment Decisions of Working Professionals: The Mediating Role of Trust and Perceived Advice Quality in Stock Market Participation (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
This study investigates the burgeoning influence of YouTube-based financial  influencers (“finfluencers”) on the investment behaviors of working professionals.  As digital platforms democratize financial advice, understanding the cognitive  and psychological drivers of investment becomes paramount. Grounded in Source  Credibility Theory (SCT), this research examines how influencer content drives  stock market participation through two critical mediators: Trust and Perceived  Advice Quality. A quantitative study was conducted using a hypothetical sample  of 400 working professionals across urban centers. The findings indicate that  while direct “trading tips” stimulate immediate investment intent, long-term and  sustained stock market participation are heavily dependent on the established  trust between the viewer and the influencer. Furthermore, perceived advice  quality acts as a secondary mediator, ensuring that professionals feel competent in  their decision-making. The results underscore a significant shift from traditional  institutional advisory to social-media-driven peer advisory. This paper contributes  to behavioral finance literature by identifying the “Trust-Quality” bridge in digital  ecosystems and suggests that regulatory bodies should focus on the quality metrics  of digital financial content to protect retail investors.
Keywords: YouTube Finfluencers; Source Credibility Theory; Trust; Perceived Advice Quality; Stock Market Participation; Behavioral Finance